2022
DOI: 10.37080/nmj.124
|View full text |Cite
|
Sign up to set email alerts
|

Denture hygiene habit and denture care practice in complete denture wearing patients visiting a dental college

Abstract: Introduction: Dental wastes are discarded materials after dental treatment which includes sharp instruments, infectious waste and body fluid, human parts, toxic agents, chemical, plastics body fluid etc. which are hazardous to health if not managed and disposed in proper way. So, dentists should manage such waste properly. This study was aimed to assess knowledge, attitude and practice of dental practitioners in and surrounding district of Chitwan. Methods: This study was descriptive, cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…[14][15][16][17] The authors previously performed a study observing the denture hygiene habit and denture care practice among the complete denture wearer. 18 However, it is a quite known fact that the dentures are also the medium for attachment of plaque and simultaneously deposit calculus similar to the natural counterparts. 13 These denture plaque is also the source of multiple potentially harmful micro-organisms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[14][15][16][17] The authors previously performed a study observing the denture hygiene habit and denture care practice among the complete denture wearer. 18 However, it is a quite known fact that the dentures are also the medium for attachment of plaque and simultaneously deposit calculus similar to the natural counterparts. 13 These denture plaque is also the source of multiple potentially harmful micro-organisms.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12]23 Our previous study has also shown that denture wearers 52.85% of the participants had been using the same denture above 5 years. 18 Fabricating the denture in Nepal is bit expensive and due to the socioeconomic grounds and family history, the dentures might have been used for long time. 18 However, it can also be speculated that the dentures hygiene had also not been maintained.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations